FINANCIAL TECHNOLOGY, KEMAMPUAN MANAJERIAL DAN PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KEUANGAN - Wibisono, Sukarno Himawan; Adrian Junaidar Handayanto; Fendiyatmi Kusufa; Oktavianus Wolo Wali (Jurnal Ilmu Akuntansi, 2025)
This study aims to analyze the influence of financial technology (fintech), managerial capabilities, and the application of management accounting information systems on the financial performance of Small and Medium Enterprises (SMEs). SMEs have an important role in national economic growth, but often face obstacles in financial management. Fintech is present as an innovative solution in supporting financial activities, while managerial capabilities and management accounting information systems are internal factors that affect the effectiveness of financial decision-making and control. The research method used was quantitative with a survey approach through the distribution of questionnaires to 40 SMEs. Data analysis was carried out using multiple linear regression. The results of the study show that fintech, managerial skills, and management accounting information systems simultaneously have a significant effect on the financial performance of SMEs. Partially, each variable also showed a significant positive influence. These findings imply the importance of the adoption of financial technology and the improvement of managerial competence and the implementation of the right information system in supporting the financial sustainability of SMEs.